Prospects for radical emissions reduction through behavior and lifestyle change. Issue 4 (4th July 2014) - Capstick, Stuart; Lorenzoni, Irene; Corner, Adam; Whitmarsh, Lorraine
Abstract : Over the past two decades, scholars and practitioners across the social sciences, policy and beyond have proposed, trialled and developed a wide range of theoretical and practical approaches designed to bring about changes in behaviors and lifestyles that contribute to climate change. With the exception of the establishment of a small number of iconic behaviors such as recycling, it has, however, proved extremely difficult to bring about meaningful transformations in personal greenhouse gas emissions at the individual or societal level, with multiple reviews now pointing to the limited efficacy of current approaches. We argue that the majority of approaches designed to achieve mitigation have been constrained by the need to operate within prevailing social scientific, economic and political orthodoxies which have precluded the possibility of non-marginal change. In this paper, we ask what a truly radical approach to reducing personal emissions would look like from social science perspectives which challenge the unstated assumptions severely limiting action to date, and which explore new alternatives for change. We emphasize the difficulties likely to impede the instituting of genuinely radical societal change with respect to climate change mitigation, while proposing ways that the ground could be prepared for such a transformation to occur.